Acute leukemia and SARS-CoV-2 infection: clinical characteristics and risk factors for mortality. Issue 14 (6th December 2021) - Mitrovic, Mirjana; Pantic, Nikola; Sabljic, Nikica; Vucic, Miodrag; Bukumiric, Zoran; Virijevic, Marijana; Pravdic, Zlatko; Rajic, Jovan; Todorovic-Balint, Milena; Vidovic, Ana; Suvajdzic-Vukovic, Nada
Abstract: Patients with acute leukemia (AL) have a high mortality rate from coronavirus disease 2019 (COVID-19). However, studies including patients with AL and COVID-19 are few. Fifty-one patients with AL and COVID-19 were included in our study. The mortality rate was 17/51 (29.4%). In all cases, death was associated with COVID-19 pneumonia. The major driver of outcome was the disease status (worse outcome was observed in newly diagnosed (OR, 6.00; 95% CI, 1.133 – 15.188) and patients with bone marrow aplasia (OR 4.148 [95% CI 1.133 – 15.188])). Higher mortality rate was associated with lower platelet count, prolonged PT, higher ISTH DIC score, CRP and LDH. Moreover, careful risk-benefit assessment regarding the continuation of anticancer therapy is required in patients receiving nonintensive and supportive therapy. Considering the high frequency of intrahospital viral transmission (50.98%), isolation of AL patients in single rooms, and permanent symptom monitoring and testing should be prioritized.